Numerical study of surfactants’ effect in surface agglomeration during 3D nano-inkjet printing by many-body dissipative particle dynamics - Aphinyan, Suphanat (2018)
Surfactants are necessary in very small scale 3D inkjet printing in order to control and reduce agglomeration leading to nozzle clogging. This numerical study specially focuses on nano-droplet formation that takes place at the nozzle. As nano-droplet formation can be modelled by Many-Body Dissipative Particle Dynamics (MDPD), this methodology is employed for the implementation surfactants to study its performance on reducing agglomeration and effects on nano-droplet formation. The surfactant is implemented in MDPD as a simple molecule composing of single hydrophilic bead and single hydrophobic bead. Additional attraction parameters to properly implement the surfactants are a major feature of this study. Present findings indicate that a sufficient small amount of surfactant can effectively reduce ink deposition on the nozzle wall, in line with actual commercial references. From this work, we can conclude that the MDPD is an appropriate meso-scale simulation technique to numerically study nano-scale 3D inkjet flow dynamics, and to predict associated trends.